Design Of Linear Polarization Antenna For Wireless MIMO Application - Abd Rashid, Kamarul Ariffin; Husain, Mohd Nor; Othman, Abdul Rani; Abd Aziz, Mohamad Zoinol Abidin; Saad, M.M; Senon , M.; Ahmad , M. T.; Hamidon, J. Sam (Asian Research Publishing Network (ARPN), 2014)
-